2017
DOI: 10.1097/aci.0000000000000342
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposures and the development of childhood wheezing illnesses

Abstract: Purpose of review To critically evaluate and summarize studies published between July 2015 and June 2016 linking prenatal exposures and the onset of childhood wheezing illnesses, and to discuss future research directions in this field. Recent findings The aggregated evidence indicates a consistent detrimental effect of prenatal exposure to parental smoking, outdoor air pollution, and maternal stress on childhood wheezing illnesses. Less consistent evidence suggests an adverse impact of maternal obesity durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 35 publications
0
19
0
1
Order By: Relevance
“…Early life exposure in utero can affect fetal airway and lung development, as well as immune function. 30 As suggested by previous studies, maternal smoking, unqualified diet, vitamin D deficiency and exposure to air pollution has been found to be possible potential risk factors. 7,31−34 A retrospective follow-up study was conducted among 1201 Los Angeles women between 3 and 6 months after delivery, where it was shown that children whose mothers ate more fast food during pregnancy had a relative increased risk of asthma.…”
Section: Discussionmentioning
confidence: 76%
“…Early life exposure in utero can affect fetal airway and lung development, as well as immune function. 30 As suggested by previous studies, maternal smoking, unqualified diet, vitamin D deficiency and exposure to air pollution has been found to be possible potential risk factors. 7,31−34 A retrospective follow-up study was conducted among 1201 Los Angeles women between 3 and 6 months after delivery, where it was shown that children whose mothers ate more fast food during pregnancy had a relative increased risk of asthma.…”
Section: Discussionmentioning
confidence: 76%
“…Conversely, maternal obesity has profound effects on immune responses in the baby, giving rise to systemic inflammation as well as asthma. Maternal prenatal BMI is associated with increased incidence of wheezing and asthma …”
Section: External Influences On the Developing Immune Systemmentioning
confidence: 99%
“…Maternal stress is a significant risk factor for wheezing in early life as well as development of asthma . This may be due to transfer of glucocorticoid hormone across the placenta, which has wide ranging effects on the immune system .…”
Section: External Influences On the Developing Immune Systemmentioning
confidence: 99%
See 2 more Smart Citations